Redescription of Paraleptophlebia falcula Traver 1934 with notes on status and composition of Paraleptophlebia Lestage 1917 and Neoleptophlebia Kluge 1997 (Ephemeroptera: Leptophlebiidae) - Tiunova, Tatiana M.; Kluge, Nikita (Zootaxa, 2016)
The taxon Paraleptophlebia Lestage 1917 is accepted here in generic rank, so rank of Neoleptophlebia Kluge 1997 is also raised from subgenus to genus, and the following new combinations are proposed: Neoleptophlebia adoptiva (McDunnough 1929) comb. n., N. assimilis (Banks 1914) comb. n., N. erratica (Kang & Yang 1994) comb. n., N. heteronea (McDunnough 1924) comb. n., N. japonica (Matsumura 1931) comb. n. (= Paraleptophlebia chocolata Imanishi 1937), N. mollis (Eaton 1871) comb. n., N. memorialis (Eaton 1884) comb. n., N. spina (Kang & Yang 1994) comb. n., N. swannanoa (Traver 1932) comb. n., N. temporalis (McDunnough 1926) comb. n., N. vladivostokica (Kluge 1982) comb. n. Larvae, male and female imagoes and eggs of Paraleptophlebia falcula Traver 1934 are described based on reared specimens from Siberia and Russian Far East; larvae and eggs are described for the first time. Characters of this species agree with diagnosis of Paraleptophlebia in the restricted sense; comparison of larva of P. falcula with other known larvae of Paraleptophlebia is given. Formerly this species was known as imagoes from limited area in Western Nearctic. According to the new data, it is widely distributed in northern part of Amphipacific Sector of Holarctic, and its area includes Polar Urals (Komi Republic), Siberia (Transbaikal Kray, Sakha Yakutia and Amurskaya Oblast’ of Russia) and west of North America (Oregon, Idaho and Washington states of USA).